APPRECIATION OF PRIMARY RESECTıON IN SıGMOID COLON VOLVULUS - Ahmet KUŞDEMİR and Hakan DEMİREL and Yusuf AKİF AKGÜN and Buğra KAPTANOĞLU and Tuğbay TUĞ and Vehip ARIKAN and Kemal ALTAY (Turkish Journal of Gastroenterology, 2020)
-